Molecular characterization of closteroviruses infecting Cordyline fruticosa L. in Hawaii - Melzer, Michael; Sugano, Jari; Uchida, Janice; Borth, Wayne; Kawate, Michael; Hu, John (Frontiers in Microbiology, 2013)
In Hawaii, common green ti plants (Cordyline fruticosa L.) have been shown to harbor Cordyline virus 1 (CoV-1) which, along with Little cherry virus 1 (LChV-1) and Grapevine leafroll-associated virus 7 (GLRaV-7), form a distinct clade within the family Closteroviridae. Preliminary work has indicated that, aside from CoV-1, three additional closteroviruses may infect common green ti plants in Hawaii. In this study, pyrosequencing was used to characterize the genomes of closteroviruses infecting a single common green ti plant. The sequence data confirmed the presence of CoV-1 as well as three additional closteroviruses. Although all four viruses had the same general genome organization, the sequence divergence between the RNA-dependent RNA polymerase, heat shock protein 70 homolog, and coat protein ranged from 22 to 61%, indicating these represent four distinct closterovirus species. The names CoV-2, CoV-3, and CoV-4 are proposed for the three new viruses. Phylogenetic analyses placed CoV-2, CoV-3, and CoV-4 in the same clade as CoV-1, LChV-1, and GLRaV-7.